Pengaruh fermentasi tepung kulit kopi Oleh Aspergillus oryzae dengan penambahan dua variasi konsentrasi urea dan amonium sulfat terhadap penurunan serat kasar - salman salman; Kurniawan Sinaga; Meutia Indriana; Yessi Febriani; Zulfikar Zulfikar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The high yield of coffee causes an increase in the amount of coffee husk waste produced, so innovations are needed to process coffee waste so that it can be helpful and not wasted. The study aimed to reduce crude fiber in fermented coffee husks using Aspergillus oryzae to become animal feed. The research was conducted using experimental and descriptive methods: coffee husk flour (Coffea sp.), Aspergillus oryzae, urea, ammonium sulfate, and minerals. Coffee husk flour was fermented in dry media and wet media at room temperature for 24 hours, 48 hours, and 72 hours. After fermentation, test the analysis of the decrease in the amount of crude fiber in the sample using the Wendee method test. The results showed that the fermentation of coffee husk flour (Coffea sp.) using Aspergillus oryzae with the addition of urea, ammonium sulfate, and minerals could reduce the amount of crude fiber. The difference in fermentation media showed that fermentation in wet media gave better crude fiber reduction results than fermentation in dry media. The crude fiber yield of dry media sample N1 is 0.25 grams (25%), and sample N2 is 0.22 grams (22%), while the crude fiber yield of wet media sample N1 is 0.13 grams (13%) and sample N2 is 0.11 grams (11%). Fermentation with Aspergillus oryzae produces ligninase, an enzyme that breaks down lignin which can degrade lignin into simpler compounds.